Response to Rotenone Is Glucose-Sensitive in a Model of Human Acute Lymphoblastic Leukemia: Involvement of Oxidative Stress Mechanism, DJ-1, Parkin, and PINK-1 Proteins (2014)
ABSTRACT: To establish the effect of low (11 mM) and high (55 mM) glucose concentrations (G11, G55) on Jurkat cells exposed to rotenone (ROT, a class 5 mitocan). We demonstrated that ROT induces apoptosis in Jurkat cells cultured in G11 by oxidative stress (OS) mechanism involving the generation of anion superoxide radical (, 68%)/hydrogen peroxide (H2O2, 54%), activation of NF-B (32%), p53 (25%), c-Jun (17%) transcription factors, and caspase-3 (28%), apoptosis-inducing factor (AIF, 36%) nuclei translocation, c-Jun N-terminal kinase (JNK) activation, and loss of mitochondria transmembrane potential (, 62%) leading to nuclei fragmentation (~10% and ~40% stage I-II fragmented nuclei, resp.). ROT induces massive cytoplasmic aggregates of DJ-1 (93%), and upregulation of Parkin compared to untreated cells, but no effect on PINK-1 protein was observed. Cell death marker detection and DJ-1 and Parkin expression were significantly reduced when cells were cultured in G55 plus ROT. Remarkably, metformin sensitized Jurkat cells against ROT in G55. Our results indicate that a high-glucose milieu promotes resistance against ROT/H2O2-induced apoptosis in Jurkat cells. Our data suggest that combined therapy by using mitochondria-targeted damaging compounds and regulation of glucose (e.g., metformin) can efficiently terminate leukemia cells via apoptosis in hyperglycemic conditions.